2017
DOI: 10.1017/s1368980017001161
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-processed foods and added sugars in the Chilean diet (2010)

Abstract: In Chile, ultra-processed foods are important contributors to total energy intake and to the consumption of added sugars. Actions aimed at limiting consumption of ultra-processed foods are being implemented as effective ways to achieve WHO dietary recommendations to limit added sugars and processed foods, especially for children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
242
6
22

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(286 citation statements)
references
References 25 publications
16
242
6
22
Order By: Relevance
“…It has been noted that ultra-processed foods contribute substantially to population intakes of micronutrients across many countries (12) . Findings from the studies in this special issue challenge that assertion and demonstrate an association between higher consumption of ultra-processed foods and poorer nutritional intakes, including higher intakes of energy and free/added sugar (9,11) and lower intakes of fibre (9) , micronutrients (9) and protein (8) . Epidemiological evidence has previously demonstrated that ultra-processed food consumption is associated with poorer diet quality in the USA (13) , Canada (14) and Brazil (15) ; obesity in Brazil (16) , Guatemala (17) , Spain (18) and Sweden (19) ; hypertension in Spain (20) ; metabolic syndrome in Brazil (21) ; and dyslipidaemia in children in Brazil (22) .…”
mentioning
confidence: 74%
“…It has been noted that ultra-processed foods contribute substantially to population intakes of micronutrients across many countries (12) . Findings from the studies in this special issue challenge that assertion and demonstrate an association between higher consumption of ultra-processed foods and poorer nutritional intakes, including higher intakes of energy and free/added sugar (9,11) and lower intakes of fibre (9) , micronutrients (9) and protein (8) . Epidemiological evidence has previously demonstrated that ultra-processed food consumption is associated with poorer diet quality in the USA (13) , Canada (14) and Brazil (15) ; obesity in Brazil (16) , Guatemala (17) , Spain (18) and Sweden (19) ; hypertension in Spain (20) ; metabolic syndrome in Brazil (21) ; and dyslipidaemia in children in Brazil (22) .…”
mentioning
confidence: 74%
“…Further, many existing studies acknowledged the use of a dietary assessment methods not designed for assessment of food processing as an important study limitation [18, 33, 36, 49, 55, 56, 61, 77]. The lack of specificity of FFQ food item questions may lead to misclassification of ultra-processed foods that could potentially attenuate or bias associations between these foods and health outcomes [78].…”
Section: Future Research Needsmentioning
confidence: 99%
“…This limitation extends to household expenditure surveys, which distinguish relatively few items [50]. Several studies using 24-hour dietary recalls also acknowledge that only limited information indicative of food processing is collected and collected inconsistently for different food items [36, 49]. Misclassification is particularly likely for foods such as pizza, mixed dishes, cookies, or other baked goods, which could be either culinary preparations or ultra-processed pre-prepared products [33].…”
Section: Future Research Needsmentioning
confidence: 99%
See 2 more Smart Citations